The Creative Spirit: a Research Experience in Higher Education - Piñeiro Ruiz, Milagro (2010)
This article presents a research experience carried out during the first 2009 period with students of the General Didactic course at the Universidad de Costa Rica, Sede de Occidente. This experience intends to motivate students’ creativity for the construction of their own didactic, through the development of two course objectives: to analyze didactic action from different approaches and to determine the relationship between didactic and educational innovations, and its association with professional culture. Diagnostic, formative and summative evaluations were used as a strategy to assess the experience.